MENINGKATKAN HASIL BELAJAR SISWA MELALAUI MODEL PEMBELAJARAN MAKE A MATCHPADA MATA PELAJARAN AGAMA KRISTEN DI KELAS IX-E SMP N 1 SIDIKALANG - Lasma Sipayung (Jurnal Guru Kita PGSD, 2018)
Abstract : Improving Student Learning Results Through Learning Model Make A Match At Religious Lessons Of Christians In Class IX-E Smp N 1 Sidikalang. This study aims to see students' learning attitudes in Christian learning by applying Make A Match learning model to media-assisted crossword puzzles in IX-E class of SMP Negeri 1 Sidikalang. The research is applied to the students of class IX-E SMP Negeri 1 Sidikalang with the number of 21 students. After two cycles of research it can be concluded that; 1) Students' learning outcomes by applying the Make a Match learning model of media crossword puzzles on the subjects of Christianity in the class IX-E SMP Negeri 1 Sidikalang, that is, in the first cycle there are 11 students who are solved individually while the class is not complete. Cycle II there are 19 students who complete the individual and the class completely, whereas in cycle II menyisahkan 2 students are not complete individually.Keywords : Learning Model Make A Match Assisted Media Crossword, Attitude LearnAbstrak : Meningkatkan Hasil Belajar Siswa Melalui Model Pembelajaran Make A Match pada Mata Pelajaran Agama Kristen di Kelas IX-E SMP N 1 Sidikalang. Penelitian ini bertujuan untuk melihat sikap belajar siswa dalam pembelajaran Agama Kristen dengan menerapkan model pembelajaran Make A Match berbantu media teka teki silangdi kelas IX-E SMP Negeri 1 Sidikalang. Penelitian dikenakan pada siswa kelas IX-E SMP Negeri 1 Sidikalang dengan jumlah 21 orang siswa. Setelah penelitian berlangsung selama dua siklus dapat disimpulkan bahwa; 1)Hasil belajar siswa dengan menerapkan model pembelajaran Make a Match berbantu media teka teki silang pada mata pelajaran Agama Kristen di kelas IX-E SMP Negeri 1 Sidikalang, yaitu, pada Siklus I terdapat 11 orang siswa yang tuntas secara individu sedangkan kelas tidak tuntas. Siklus II terdapat 19 siswa yang tuntas secara individu dan kelas tuntas, sedangkan pada siklus II menyisahkan 2 orang siswa tidak tuntas secara individu.Kata Kunci : Model Pembelajaran Make A Match Berbantu Media Teka Teki Silang, Sikap Belajar.